Effects of hydrodynamic cavitation on physicochemical structure and emulsifying properties of tilapia (Oreochromis niloticus) myofibrillar protein - Hou, Yucheng; Ren, Xian’e; Huang, Yongchun; Xie, Kun; Wang, Keyao; Wang, Liyang; Wei, Fengyan; Yang, Feng (Frontiers in Nutrition, 2023)
The purpose of this research was to explore the different hydrodynamic cavitation (HC) times (0, 5, 10, 15, 20 min; power 550 W, pressure 0.14 MPa) on the emulsifying properties of tilapia myofibrillar protein (TMP). Results of pH, particle size, turbidity, solubility, surface hydrophobicity and reactive sulfhydryl group indicated that HC changed the structure of TMP, as confirmed by the findings of intrinsic fluorescence and circular dichroism spectra. Furthermore, HC increased the emulsifying activity index significantly (P < 0.05) and changed the emulsifying stability index (ESI), droplet size and rheology of TMP emulsions. Notably, compared with control group, the 10-min HC significantly decreased particle size and turbidity but increased solubility (P < 0.05), resulting in accelerated diffusion of TMP in the emulsion. The prepared TMP emulsion showed the highest ESI (from 71.28 ± 5.50 to 91.73 ± 5.56 min), the smallest droplet size (from 2754 ± 110 to 2138 ± 182 nm) and the best rheological properties, as demonstrated by the microstructure photographs. Overall, by showing the effect of HC in improving the emulsifying properties of TMP, the study demonstrated HC as a potential technique for meat protein processing.